The Symbolic Meaning of the Tradition “Hantaran Jamba Badagang” in a Wedding Party Ceremony at Kambang Lengayang sub-district, Pesisir Selatan - Mega Silvia Nengsih; Syafwandi Syafwandi (Postgraduate School, Universitas Negeri Padang, 2020)
This article aims to describe the shape and meaning of symbols on the delivery of Jamba Badagang in a wedding party ceremony. The approach used to parse the results of this research were the approach of art, culture, semiotics and aesthetics. The research method used descriptive qualitative. Data collection done by Observation (documentation) and Interview (Interview). Data analysis techniques used Miles and Huberman data analysis models, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that the tradition of the Hantaran Jamba Badagang was a symbol of interaction, communication, and social value. This tradition also contains the meaning of unity between communities and educational values. Furthermore, the Jamba Badagang tradition continues to be preserve and develope into the cultural heritage of the Kambang nagari community.